2019
DOI: 10.1155/2019/5480913
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in Theory of Mind in Parkinson’s Disease Is Explained by Deficits in Inhibition

Abstract: Objective. Several studies have reported that people with Parkinson’s disease (PD) perform poorly on tests of ‘Theory of Mind’ (ToM), suggesting impairment in the ability to understand and infer other people’s thoughts and feelings. However, few studies have sought to separate the processes involved in social reasoning from those involved in managing the inhibitory demands on these tests. In this study, we investigated the contribution of inhibition to ToM performance in PD. Methods. 18 PD patients and 22 age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 64 publications
1
21
0
4
Order By: Relevance
“…Although executive abilities were not directly measured, executive dysfunction is common in idiopathic dystonia [29], and may partly explain our participants' poorer performance on the ToM reality-known task. In Parkinson's disease patients, performance on a ToM task worsened when self-perspective inhibitory demands were high, in association with executive control measures [30]. Future , the model statistic reported is chi-squared and the predictor b is the exponentiation of the b coefficient, which can be interpreted as an odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Although executive abilities were not directly measured, executive dysfunction is common in idiopathic dystonia [29], and may partly explain our participants' poorer performance on the ToM reality-known task. In Parkinson's disease patients, performance on a ToM task worsened when self-perspective inhibitory demands were high, in association with executive control measures [30]. Future , the model statistic reported is chi-squared and the predictor b is the exponentiation of the b coefficient, which can be interpreted as an odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked performance of PD patients on affective ToM tasks with other cognitive deficiencies, including visuospatial ability, inhibition, cognitive flexibility, and working memory [ 23 , 27 , 75 ]. Although we found that differences in ToM performance between EOPD and controls were not mediated by overall cognitive ability, deficiencies in specific cognitive domains could have impacted performance in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have centered on the same SC domains [ 23 , 24 ]. Their findings demonstrate consistent deficits in ToM, especially cognitive ToM [ 23 , 25 , 26 ], although a growing body of evidence shows that affective ToM is also compromised [ 25 , 27 , 28 ]. Furthermore, deficits in ToM appear to be present even in the early stages of the disease [ 29 ] and worsen with disease progression [ 28 ] and are not associated with dopamine-based therapy [ 26 ].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations